Maternal Mortality : Report June, 1932 (London : The Maternal Mortality Committee)
1932-06 1932 1930s 20 pages It is obvious that though the number of ante-natal clinics is increasing there are still not enough. We note that many Medical Officers of Health comment on the increased demand for ante-natal treatment. The Medical Officer for Flintshire reiterates the need for ante-natal observation beds, pointing out that the work of the ante-natal centre is hampered by the fact of lack of accommodation in the Maternity Home. The Medical Officer for Carmarthenshire speaks of the crying need for a central Maternity Home, while out of many others showing the importance of ante-natal care we can instance the strong passage in the Report from Glamorgan, and an illuminating sentence from Cardiff. The Medical Officer for Glamorgan points out that "the majority of expectant mothers are not yet receiving the necessary advice and supervision during pregnancy, although agreement about the desirability of this is gaining ground steadily among women." In Flintshire, "the mothers are realising more and more that ante-natal care of their health is of vital importance. They are seeking in greater numbers, and with greater seriousness, antenatal care at the clinics." Holland (Lincs) reports :— Ante-natal Supervision. This can be done at ante-natal centres but none of the County Centres are suitably equipped, and even if this could be arranged it is impracticable for the majority of women concerned to attend the Centres. Arrangements should therefore be made with private medical practitioners to undertake the routine ante-natal examination of uninsured women who have engaged midwives for the confinement. The same evidence comes from the County Boroughs. At Tynemouth a scheme is under consideration similar to that mentioned in the Holland (Lincs) report. The Medical Officer of Newcastle-on-Tyne states that over 60 per cent. of the mothers are attending the ante-natal centre. Salford reports insufficient accommodation at the ante-natal clinic, while in Stockport the ante-natal clinics have increased from one bi-weekly to four per week, and the attendances from sixty-one in 1925 to 920 in 1930, some midwives bringing as many as 87 per cent. of their cases to the clinics. Hull states that of 2,015 women who attended the ante-natal clinics there were only three deaths. It is interesting to contrast the result here with that at St. Helens, where, reporting six fatal cases of toxaemias of pregnancy, the M.O. says, "The mothers are not entirely to blame [for not insisting on ante-natal care] as five out of six cases attended their own medical practitioner previous to confinement and in only one case was the urine examined." (13) 292/824/1/58